Meaning of Happy Life for the Kharwars in India in Their Journey Towards Development. (September 2017) - Mishra, R. C.
The study examines the notion of happy life and its ingredients in a rural adivasi (first nation people) community experiencing the influences of acculturation and development taking place in the rapidly globalising world. The study was carried out on 200 males of the Kharwar adivasi group residing in 11 villages of the Naugarh Block of Chanduali district in Uttar Pradesh. The participants, aged 30–60 years, were given the happy life test (Sinha, 1969, Indian villages in transition: A motivational analysis . Delhi: Associated Publishing House) with slight modification in the questions. Content analysis of responses brought out five major elements of happy life, namely economy, relationships, health, meaningful engagements and money. Cluster analysis revealed that only economy, relationships and health were reliable elements of happy life, while the other two elements were outliers. As compared to the happy Kharwars, the less happy Kharwars suggested more number of items as ingredients of happy life. The findings suggest that the ingredients of happy life are culture specific and not universal. It is suggested that, even in the face of a development model, which underscores material possessions, the life of people in traditional societies, such as of the Kharwar, is driven largely by need rather than by greed.